2006
DOI: 10.1111/j.1365-2133.2006.07128.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermal nickel exposure associated with coin handling and in various occupational settings: assessment using a newly developed finger immersion method

Abstract: We describe a reproducible, simple and rapid procedure for the assessment of nickel levels in occupationally exposed individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 23 publications
2
49
1
Order By: Relevance
“…However, most studies performed to date have used similar numbers of coins, or fewer coins and volunteers (16,(26)(27)(28). We consider the results to be reliable, and believe that they can be generalized.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 68%
See 1 more Smart Citation
“…However, most studies performed to date have used similar numbers of coins, or fewer coins and volunteers (16,(26)(27)(28). We consider the results to be reliable, and believe that they can be generalized.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 68%
“…Cashiers in Sweden received a mean nickel skin dose of 0.2 μg/cm 2 per hour at work (16), measured with the acid wipe sampling method, as in the present study. Cashiers in the United Kingdom received mean skin doses of 0.03 and 0.2 μg/cm 2 after at least 1 hr of work, as measured with finger immersion in ultra-pure water (26,27). The recently introduced nickel-plated steel coins deposited higher doses of nickel on skin than those found in all other available studies on coin handling.…”
Section: Interpretation With Reference To Other Studiesmentioning
confidence: 98%
“…Inhalation is the primary route of occupational exposure to metals [2]. The studies relating to occupational exposure to Ni during nickelplating process have shown that nasal toxicity [3], nickel dermatitis [4], allergic contact dermatitis and hand dermatitis [5][6][7], occupational asthma [8], mortality due to stomach cancer and lung cancer [9] and renal tubular dysfunction [10] have been observed in nickelplating workers. Exposure to Ni has been shown to result in an increased level of trypsin and a decreased level of carboxypeptidase B in the pancreatic tissue of animals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in techniques have better quantified the skin levels of nickel required to elicit an allergic reaction (5,6). On a European level, attempts have been made to minimize the risks through the Nickel Directive and REACH, its successor from 2009 (7,8).…”
mentioning
confidence: 99%
“…One of the well-recognized features of coin handling is that there is a rapid increase in the skin levels of nickel on handling the coins seen over a short time of seconds to minutes (6). Thus a true test for risk assessment in this area is one that reproduces as near as possible the situation found in day-to-day handling of coins by professions such as cashiers or bank workers (and consumers), supported by the measurement of nickel levels on the skin surface over time points.…”
mentioning
confidence: 99%